2018
DOI: 10.3390/ijms19061736
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Protects Human Retinal Pigment Epithelial Cells from Hydrogen Peroxide-Induced Oxidative Damage through Activation of AMPK

Abstract: Age-related macular degeneration (AMD) is the leading cause of central vision loss in the elderly with less effective treatment, especially for dry AMD (90% of AMD). Although the etiology of this disease is not well elucidated, increasing evidences indicate that excessive reactive oxygen species (ROS) impairing the physiological functions of retinal pigment epithelium (RPE) cells may be one of the main causes. Therefore, it could be a great strategy to find some drugs that can effectively protect RPE cells fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 60 publications
1
32
0
Order By: Relevance
“…This process involves transportation of oxygen and nutrients, uptake of circulating vitamin A, elimination of wastes of photoreceptors metabolism and secretion of essential factors for facilitating the regeneration and repair of retina 19 . It is found that the retina contains highest oxygen consumption than other tissues, which suggests that RPE cells are susceptible to oxidative stress, particularly when exposed to high levels of reactive oxygen species (ROS) 20 . Furthermore, RPE is lack of ability to renew itself following differentiation 7 and the resistance of the antioxidant system of RRE decreases in the elderly population 21 .…”
Section: Discussionmentioning
confidence: 99%
“…This process involves transportation of oxygen and nutrients, uptake of circulating vitamin A, elimination of wastes of photoreceptors metabolism and secretion of essential factors for facilitating the regeneration and repair of retina 19 . It is found that the retina contains highest oxygen consumption than other tissues, which suggests that RPE cells are susceptible to oxidative stress, particularly when exposed to high levels of reactive oxygen species (ROS) 20 . Furthermore, RPE is lack of ability to renew itself following differentiation 7 and the resistance of the antioxidant system of RRE decreases in the elderly population 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Gene silencing by shRNA was performed as previously described [ 29 ]. Before the experiment, transfection complexes were made by mixing shRNA with Lipo2000 and Opti-MEM followed by incubation for 15 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Another in vitro model was the application of tert -butyl hydroperoxide on human fetal RPE and APRE-19 cells [ 57 ]. Moreover, a hydrogen peroxide-induced AMD cellular model has also been used to test the therapeutic efficacy of piceatannol [ 58 ], scutellarin [ 59 ], and berberine [ 60 ].…”
Section: Disease Mechanisms Of Amdmentioning
confidence: 99%